THE DETERMINATION OF BARIUM STRONTIUM TITANATE THIN FILM BAND GAP ENERGY Ba0,15Sr0,85TiO3 USING ULTRAVIOLET-VISIBLE SPECTROSCOPY - Rahmi Dewi; Krisman Krisman; Zulkarnaen Zulkarnaen; Rahmi Afrida Syahraini; TS Luqman Husein (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
A thin layer of Barium Strontium Titanate Ba0.15Sr0.85TiO3 (BST) was developed on a glass substrate using a sol-gel method with annealing temperatures and spin coating process at 3500 rpm for 30 seconds. The annealing temperature varied from 600oC, 650oC, and 700oC. Characterization of optical properties was developed using UV-Vis spectroscopy to determine the energy bandgap. The values of the BST thin layer energy band at the annealing temperature were 3.55 eV, 3.32 eV, and 3.10 eV, respectively. The results indicate that the BST thin film was a semiconductor material.